2020
DOI: 10.1302/2058-5241.5.190064
|View full text |Cite
|
Sign up to set email alerts
|

Sacral fractures: issues, challenges, solutions

Abstract: Sacral fractures are a heterogeneous group of fractures occurring in young people following road traffic accidents and falls from height, or in the elderly with osteoporosis following trivial trauma. This heterogeneity, combined with the low incidence of sacral fractures, determines a lack of experience amongst physicians, often leading to misdiagnosis, underestimation and inadequate treatment. The diagnosis should be made by assessing specific features during the clinical presentation, while computed tomograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 124 publications
1
46
0
4
Order By: Relevance
“…While high-energy elderly sacral fractures are more likely to be treated surgically in comparison to low-energy fractures, given that reduction is often necessary, these outcomes suggest similar success across both demographics. 15 With respect to living or residential status, 94.9% of patients in the current study who had been living independently preinjury returned to their same residential living status by last follow-up. The relative change in residential living status from pre-injury to post-surgery was statistically significant, such that those living independently prior to injury had a greater likelihood of living independently following surgery than those who were in assisted living facility pre-injury (p ¼ 0.02).…”
Section: Discussionmentioning
confidence: 69%
“…While high-energy elderly sacral fractures are more likely to be treated surgically in comparison to low-energy fractures, given that reduction is often necessary, these outcomes suggest similar success across both demographics. 15 With respect to living or residential status, 94.9% of patients in the current study who had been living independently preinjury returned to their same residential living status by last follow-up. The relative change in residential living status from pre-injury to post-surgery was statistically significant, such that those living independently prior to injury had a greater likelihood of living independently following surgery than those who were in assisted living facility pre-injury (p ¼ 0.02).…”
Section: Discussionmentioning
confidence: 69%
“…The role of external fixation alone for treatment of pelvic fractures is now limited to the emergency management of hemodynamic instability. 1,2 Acute surgical decompression of sacral nerve roots is associated with risk of bleeding, wound complications and CSF leak however, surgery is considered if there is a chance to restore even a unilateral distal root function for voluntary bowel and bladder control. Neurological improvement of up to 80% is frequent, regardless of the type of operative or conservative management.…”
Section: Discussionmentioning
confidence: 99%
“…Spinopelvic dissociation associated with neurologic lesions hardly ever recover completely, with residual lower-limb neurologic deficits, urinary problems and sexual dysfunction. [1][2][3] Three cases in our study had preoperative L5-S1 neurologic deficit that showed improvement after reduction and fixation of their Denis-II sacral fractures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wenn möglich, sollten, wie in unserer Arbeitsgruppe üblich, die Therapiekonzepte in einer interdisziplinären Fallkonferenz festgelegt werden. Für dislozierte instabile Beckenfrakturen kommt nur die Operation unter Berücksichtigung einer Vielzahl von osteosynthetischen Techniken infrage [13,41,43,86].…”
Section: Diskussionunclassified